Promoting spontaneous focusing on numerosity and cardinality-related skills at day care with one, two, how many and count, how many programs. Issue 4 (1st October 2020) - Hannula-Sormunen, Minna; Nanu, Cristina; Luomaniemi, Katri; Heinonen, Milja; Sorariutta, Anne; Södervik, Ilona; Mattinen, Aino
ABSTRACT: In this study we investigated the effects of two naturalistic 2- to 4-year-old children's intervention programs aimed at promoting children's Spontaneous Focusing On Numerosity (SFON) and early numerical skills. The study consisted of a quasi-experimental, pretest-posttest design with a delayed posttest and an active control group participating in the Let's Read and Talk program. All conditions had 6 weeks of intensive training followed by a 4-month rehearsal phase, when intervention activities were integrated into normal day care. The results of both numerical interventions in the whole group level show positive, small- to medium-sized long-term effects on cardinality-related skills from pretest to delayed posttest. The SFON tendency increased more from pretest to posttest in both studies but the group differences vanished in the delayed posttest. The children in the Count, how many programs developed more in SFON tendency from pretest to posttest, while the better development of SFON from pretest to posttest was significant only for the low group in the One, two, how many programs. There were no group differences in vocabulary or story comprehension skills. Educational implications suggest that combining SFON and cardinality-related skill training at day care results in developmentally effective activities for early educators and children.